PELATIHAN PENYUSUNAN MENU SEHAT SEIMBANG BAGI GURU PAUD DI TULANG BAWANG BARAT PROVINSI LAMPUNG - Asih Budi Kurniawati; Devi Nawangsasi; Een Yayah Haenilah (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Malnutrition and obesity are health problems that often occur in society due to an imbalance in the intake of nutrients consumed. Community service with balanced healthy menu counseling activities aims to prevent health problems of malnutrition and obesity that are rife in the community. The method used in this community service activity is an informative - participatory method with the technique of delivering training materials on general guidelines for balanced nutrition. Balanced menu counseling activities were given to 30 PAUD teachers in the West Tulang Bawang area. Post test results of participants who were able to answer all the questions given were 32%. This shows that there is a significant increase in the knowledge of PAUD teachers.